Hermite-Hadamard-type inequalities for r-convex functions using Riemann-Liouville fractional integrals - Deng, J.; Fečkan, M.; Wang, J. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
By using two fundamental fractional integral identities, we derive some new Hermite – Hadamard-type inequalities for differentiable r-convex functions and twice-differentiable r-convex functions involving Riemann – Liouville fractional integrals.